Genetic profile of Brazilian patients with dystrophinopathies. Issue 2 (22nd February 2017) - de Almeida, P.A.D.; Machado‐Costa, M.C.; Manzoli, G.N.; Ferreira, L.S.; Rodrigues, M.C.S.; Bueno, L.S.M.; Saute, J.A.M.; Pinto Vairo, F.; Matte, U.S.; Siebert, M.; Cossio, S.L.; Macedo, G.S.; et al.
Abstract : Different types of mutations in the DMD gene underlie Duchenne muscular dystrophies (DMD) and Becker muscular dystrophies (BMD). Large deletions and duplications are the most frequent causative genetic alterations worldwide, but little is known about DMD/BMD genetic profile in Brazil. Hence, we recruited patients with DMD and BMD from 8 neuromuscular reference centers along the country, and performed a comprehensive molecular investigation that included Multiplex Ligation‐dependent Probe Amplification and Next generation sequencing (NGS) analyses. We evaluated 199 patients from 177 unrelated families: 166 with DMD, 32 with BMD and 1 1.5 years old asymptomatic patient with persistent hiperCKemia. Overall, large deletions (58.2%) followed by nonsense mutations (12.4%) and large duplications (11.3%) were the most frequent variants in Brazilian families. Large deletions were less frequent in BMD than in DMD (44.8% vs 60.8%). We identified 19 new DMD variants. Nonsense mutations were significantly more frequent in patients from northeastern region than from southern/southeastern regions of Brazil (27.7% vs 8.5%, P  < .05). Genetic profile of Brazilian patients with DMD/BMD is similar to previously reported cohorts, but it is not uniform across the country. This information is important to plan rational clinical care for patients in face of the new coming mutation‐specific therapies. Abstract :